Analisis Pengaruh Internet Banking dan Mobile Banking Terhadap Kinerja Keuangan Perbankan (Studi Empiris Perbankan Himbara Periode 2014-2023) - Anisa Juliastuty Cahyaningrum; Imron Rosyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Currently, technology and information have entered the fourth industrial revolution, which has caused its development to be very rapid and its distribution is unlimited. The financial industry or what is generally called Financial Technology (Fintech) is greatly affected by the advancement of information and technology. Fintech or financial technology plays a significant role in the economy, especially in the banking industry. Collaboration between banks and fintech companies will provide benefits for all parties, especially in terms of improving financial performance. To ascertain how internet and mobile banking relate to the financial performance of Himbara banking, this study was conducted. Using quantitative research methodology, the results of this study were obtained from data analysis and displayed as numeric values. The population of this study were all banks registered with Himbara banks, and used purposive sampling and secondary data. Three banks from Himbara (Bank BRI, Bank BNI, and Bank Mandiri) became the research samples, covering the years 2014–2023. Especially in Indonesia, the findings of this study can help banks, academics, and policy makers in utilizing financial technology to improve banking financial performance.